Impact of pH on the Phytochemical Profile of Pasteurized Peach Purée during Storage - Oliveira, Ana (2015)
Peach purée was exposed to different pH (2.5, 3.0, 3.5, 4.0, and 4.5) conditions, and its phytochemical alteration was estimated after fruit pasteurization and over a 90 day storage period at both 4 and 23 °C. During the 90 day storage, the study demonstrated a decrease in total antioxidant activity of 34−40% and a decrease in total phenolics of 18−20% at 4 °C and the corresponding decreases at 23 °C were 55−56 and 30−40%, respectively. Neochlorogenic acid (34 and 27%) and chlorogenic acid (34 and 37%) presented lower retention at the higher pH (4.5) for both storage temperatures. The degradation of carotenoids was higher at pH of 4.0 and 4.5, and the highest retention was obtained at pH 3.0 and 3.5. Zeaxanthin was the carotenoid most affected with loses of 60−68% at 4 °C and 56−75% for 23 °C. Storage time and temperature were critical factors for peach purée phytochemical profile, more than pH variation.